1, 1, 2, 2-Tetrahydroperoxy-1, 2-diphenylethane as new oxidant for chemoselective and catalyst free oxidation of sulfides to sulfoxides and sulfones. (4th March 2017) - Khosravi, Kaveh; Naserifar, Shirin; Mahmoudi, Boshra; Khalaji, Kobra
GRAPHICAL ABSTRACT: ABSTRACT: A catalyst free and chemoselective oxidation of sulfides to sulfoxides or sulfones was developed using 1, 1, 2, 2-tetrahydroperoxy-1, 2-diphenylethane as a new oxidant. This scope has shown the achievement of various sulfoxides and sulfones which were obtained selectively in high yields at room temperature.